Reimagining information science and technology beyond traditional boundaries in the global coronavirus pandemic situation. Issue 1 (22nd October 2020) - Rorissa, Abebe; Li, Ming; Young, Michael; Turetsky, David; Yuan, Xiaojun (Jenny)
Abstract: Information pervades today's human activities, essentially making every sector of society an information environment. Due to the ubiquity of technological innovations and their interconnectivity, there is no aspect of lives of individuals that has not been affected. Individuals & organizations use multiple devices and networking platforms to interact with each other, businesses, and governments, as well as to search, retrieve, and consume information. Adoption and use of information and communication technologies (ICTs) and the nature of information in general and its management and use have been topics of discussion at events such as the ASIS&T Annual Meeting. However, what is often lacking, if not missing, is a broader discussion about information and ICTs, in applied areas such as emergency management, homeland security, and cybersecurity.